Pengaruh Media Pembelajaran Berbasis PhET Simulation terhadap Hasil Belajar Mahasiswa Teknik Elektro pada Mata Kuliah Rangkaian Listrik - Dzikra Bani Doniya Habibillah; Mukhlidi Muskhir (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Education is an important aspect in improving the quality of human resources, especially in higher education in the field of engineering where a deep understanding of technical material is needed. The Electrical Circuit course is often a challenge because there are many abstract concepts that are difficult for students to understand. This study aims to analyze the effect of using PhET Simulation as a technology-based learning media to improve the learning outcomes of Electrical Engineering students in the Electrical Circuit course, as well as evaluating its ability to increase student involvement and become an alternative to limited laboratory experiments. The study used a One-Group Pretest-Posttest design with a sample of 30 students. Data was collected through pretest and posttest, then analyzed using N-Gain test. The results showed that there was a significant increase in the average student score from 59.07 in the pretest to 81.87 in the posttest, with an N-Gain score of 0.55 which was included in the moderate category. This finding proves that PhET Simulation is effective in improving the understanding of Electrical Circuit concepts, as well as increasing student engagement through interactive learning. This simulation also provides flexibility in conducting virtual experiments, so it can be a solution to the limitations of physical laboratories.